Long non-coding RNA RP11-283G6.5 confines breast cancer development through modulating miR-188-3p/TMED3/Wnt/β-catenin signalling. (15th October 2021) - Pei, Jing; Zhang, Shengquan; Yang, Xiaowei; Han, Chunguang; Pan, Yubo; Li, Jun; Wang, Zhaorui; Sun, Chenyu; Zhang, Jing
ABSTRACT: The contributions of long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) to breast cancer are critical areas of investigation. In this study, we identified a novel lncRNA RP11-283G6.5 which was lowly expressed in breast cancer and whose low expression was correlated with poor overall survival and disease-free survival of breast cancer patients. Functional experiments revealed that ectopic expression of RP11-283G6.5 confined breast cancer cellular growth, migration, and invasion, and promoted cellular apoptosis. Conversely, RP11-283G6.5 silencing facilitated breast cancer cellular growth, migration, and invasion, and repressed cellular apoptosis. Moreover, RP11-283G6.5 was found to confine breast cancer tumour growth and metastasis in vivo . Mechanistically, RP11-283G6.5 competitively bound to ILF3, reduced the binding of ILF3to primary miR-188 (pri-miR-188), abolished the suppressive effect of ILF3 on pri-miR-188 processing, and therefore promoted pri-miR-188 processing, leading to the reduction of pri-miR-188 and the upregulation of mature miR-188-3p. The expression of RP11-283G6.5 was significantly positively correlated with that of miR-188-3p in breast cancer tissues. Through increasing miR-188-3p, RP11-283G6.5 decreased TMED3, a target of miR-188-3p. RP11-283G6.5 further suppressed Wnt/β-catenin signalling via decreasing TMED3. Rescue assays revealed that inhibition of miR-188-3p, overexpression of TMED3 or blocking Wnt/β-catenin signalling all attenuated the roles of RP11-283G6.5 in breast cancer. Collectively, these findings demonstrated that RP11-283G6.5 is a tumour suppressive lncRNA in breast cancer via modulating miR-188-3p/TMED3/Wnt/β-catenin signalling. This study indicated that RP11-283G6.5 might be a promising prognostic biomarker and therapeutic target for breast cancer.